Buying Iintention Dilihat Dari Celebrity Endorsement Dengan Self Brand Connection Sebagai Variabel Mediasi Pada Smartphone OPPO Di Risal Cell Solok Selatan - Febsri Susanti; Feja Lajmi Marahmi; Doni Marlius (JURNAL PUNDI, 2022)
This study aims to explain the effect of celebrity endorsement on buying intention through self brand connection on Oppo smartphones in Risal Cell, South Solok. The population of this study is OPPO Smartphone users in South Solok who are consumers who have purchased Oppo cellphones in South Solok Cellular Risal involving 87 respondents. Respondents were selected using accidental sampling technique and using the Slovin formula. This research uses quantitative research methods. The data obtained from primary data is through the distribution of questionnaires to respondents. The questionnaire was tested using validity and reliability tests to determine the accuracy and consistency of the questionnaire. Furthermore, the data collected from the questionnaire were analyzed using path analysis techniques. The results showed that Celebrity endorsement had a positive and significant effect on buying intention in Oppo Smartphones. Self brand Connection mediates Celebrity endorsement of Buying Intention on Oppo Smartphones.